Improving oxidation resistance property of single-crystal Ni-based superalloy via utilizing high temperature aging-induced dislocations - Boxuan Du; Yi Ru; Jiao Wen; Xuetao Li; Yang Cao; Yunpeng Hu; Fan Yang; Yanling Pei; Shusuo Li; Shengkai Gong (Journal of Materials Research and Technology)
It is hard to improve the oxidation resistance property of single-crystal (SC) Ni-based superalloys except for alloying design since monocrystalline lacks defects such as grain boundaries that are beneficial for antioxidant elemental diffusion. This work indicates that dislocations in SC superalloys have a beneficial effect on oxidation resistance. These dislocations are formed via high-temperature aging. Taking advantage of such dislocations, the sample aged exhibited an extremely low oxidation rate, and a protective α-Al2O3 layer formed rapidly at the surface instead of multilayer oxides without the aid of aging dislocations, determining the change in oxidation mechanism. The atomic-scale investigation revealed that the Al had a higher activity in aged specimens, and the dislocation from aging treatment enabled the pipe diffusion effect. Based on our results, a new route to improving oxidation resistance of SC superalloys is proposed as skilled designing of dislocations acting as Al-diffusion pipes. These findings give a new insight into recently popular “crystal defect engineering” of alloys and provide guidelines for oxidation resistance improvement of superalloy and other alloys.